Data from: Annual ring growth of a widespread high-arctic shrub reflects past fluctuations in community-level plant biomass - Le Moullec, Mathilde; Buchwal, Agata; van der Wal, Rene; Sandal, Lisa; Hansen, Brage B. (Zenodo, 2019)
1. Long time-series of primary production are rarely available, restricting our mechanistic understanding of vegetation and ecosystem dynamics under climate change. Dendrochronological tools are increasingly used instead, particularly in the Arctic – the world's most rapidly warming biome. Yet, high-latitude plant species are subject to strong energy allocation trade-offs, and whether annual allocations to secondary growth (e.g. 'tree-rings') actually reflects primary production above-ground remains unknown. Taking advantage of a unique ground-based monitoring time-series of annual vascular plant biomass in high Arctic Svalbard (78N), we evaluated how well retrospective ring growth of the widespread dwarf shrub Salix polaris represents above-ground biomass production of vascular plants. 2. Using a balanced design in permanent plots for plant biomass monitoring, we collected 30 S. polaris shrubs across five sites in each of two habitats. We established annual ring growth time-series using linear mixed-effects models and related them to local weather records and 13 years of above-ground biomass production in six habitats. 3. Annual ring growth was positively correlated with above-ground biomass production of both S. polaris (r = 0.56) and the vascular plant community as a whole (r = 0.70). As for above-ground biomass, summer temperature was the main driver of ring growth, with this ecological signal becoming particularly clear when accounting for plant, site and habitat heterogeneity. The results suggest that ring growth measurements performed on this dominating shrub can be used to track fluctuations in past vascular plant production of high-arctic tundra. 4. Synthesis. Dendrochronological tools are increasingly used on arctic shrubs to enhance our understanding of vegetation dynamics in the world's most rapidly warming biome. Fundamental to such applications is the assumption that annual ring growth reflects between-year variation in above-ground biomass production. Here we showed that ring growth indeed was a ...